Studies on miscibility of polyetherimide/polystyrene blends - Isik, Birol; Cakar, Fatih; Cankurtaran, Ozlem (YILDIZ TECHNICAL UNIV, 2022)
The miscibility behavior of the blends of Polyetherimide (PEI) and P olystyrene (PS) was studied using different experimental techniques. The intrinsic viscosities were determined for different ratios of PEI/PS blend in dilute chloroform solutions at 25 degrees C using viscometry. According to different methods proposed by Huggins, Krigbaum and Wall, Catsiff and Hewett using the experimental results of the intrinsic viscosity studies of the PEI/PS blends, some miscibility parameters were obtained. Besides, the miscibility of the PEI/PS blends was studied using Fourier Transform Infrared Spectroscopy (FT-IR) and Differential Scanning Calorimetry measurements.
Keywords: Polyetherimide; Polystyrene; Polymer blends; POLY ETHER IMIDE; POLY(ETHER IMIDE); LIQUID-CRYSTAL; COMPATIBILITY; MIXTURES; Engineering